Brief introduction to current pharmacogenomics research tools - Cha, Eun-Young; Jeong, Hye-Eun; Kim, Woo-Young; Shin, Ho Jung; Kim, Ho-Sook; Shin, Jae-Gook (Translational and clinical pharmacology, 2016)
There is increasing interest in the application of personalized therapy to healthcare to increase the effectiveness of and reduce the adverse reactions to treatment. Pharmacogenomics is a core element in personalized therapy and pharmacogenomic research is a growing field. Understanding pharmacogenomic research tools enables better design, conduct, and analysis of pharmacogenomic stud¬ies, as well as interpretation of pharmacogenomic results. This review provides a general and brief introduction to pharmacogenomics research tools, including genotyping technology, web-based genome browsers, and software for haplotype analysis. KCI Citation Count: 0